Distinct differences in immunological properties of equine orthobiologics revealed by functional and transcriptomic analysis using an activated macrophage readout system - Pezzanite, Lynn M.; Chow, Lyndah; Griffenhagen, Gregg M.; Bass, Luke; Goodrich, Laurie R.; Impastato, Renata; Dow, Steven (Frontiers in Veterinary Science, 2023)
Multiple biological therapies for orthopedic injuries are marketed to veterinarians, despite a lack of rigorous comparative biological activity data to guide informed decisions in selecting a most effective compound. Therefore, the goal of this study was to use relevant bioassay systems to directly compare the anti-inflammatory and immunomodulatory activity of three commonly used orthobiological therapies (OTs): mesenchymal stromal cells (MSC), autologous conditioned serum (ACS), and platelet rich plasma (PRP). Equine monocyte-derived macrophages were used as the readout system to compare therapies, including cytokine production and transcriptomic responses. Macrophages were stimulated with IL-1ß and treated 24 hours with OTs, washed and cultured an additional 24 hours to generate supernatants. Secreted cytokines were measured by multiplex and ELISA. To assess global transcriptomic responses to treatments, RNA was extracted from macrophages and subjected to full RNA sequencing, using an Illumina-based platform. Data analysis included comparison of differentially expressed genes and pathway analysis in treated versus untreated macrophages. All treatments reduced production of IL-1ß by macrophages. Secretion of IL-10 was highest in MSC-treated macrophages, while PRP and ACS resulted in greater downregulation of IL-6 and IP-10. Transcriptomic analysis revealed that ACS triggered multiple inflammatory response pathways in macrophages based on GSEA, while MSC generated significant downregulation of inflammatory pathways, and PRP induced a mixed immune response profile. Key downregulated genes in MSC-treated cultures included type 1 and type2 interferon response, TNF- and IL-6. PRP cultures demonstrated downregulation of inflammation-related genes IL-1RA, SLAMF9, ENSECAG00000022247 but concurrent upregulation of TNF-, IL-2 signaling, and Myc targets. ACS induced upregulation of inflammatory IL-2 signaling, TNF and KRAS signaling and hypoxia, but downregulation of MTOR signaling and type 1 interferon signaling. These findings, representing the first comprehensive look at immune response pathways for popular equine OTs, reveal distinct differences between therapies. This evidence suggests that unique patterns of macrophage transcriptomic regulation may guide selection of OTs in specific conditions. These studies address a critical gap in our understanding of the relative immunomodulatory properties of regenerative therapies commonly used in equine practice to treat musculoskeletal disease and will serve as a platform from which further in vivo comparisons may build.